2005
DOI: 10.1614/ws-04-122r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soybean row width and velvetleaf emergence time on velvetleaf (Abutilon theophrasti)

Abstract: Row spacing and the relative time of velvetleaf emergence affects the time of soybean canopy closure relative to velvetleaf, influencing the growth and development of velvetleaf. Field studies were conducted in northeastern Nebraska in 2002 and 2003 to describe velvetleaf growth as influenced by soybean presence or absence (velvetleaf grown with soybean or in monoculture), soybean row spacing (19 and 76 cm), and relative time of velvetleaf emergence. Velvetleaf seed production, leaf area (LA), and total dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…Overall the seedlings that were emerged earlier produced additional biomass. These outcomes were confirmed by the findings of Massinga et al 2001, Puricelli et al 2002and Hock et al, 2005 Leaf areas of velvetleaf plants accumulated in the third and fourth layer 77 % and 71 % for the 50cm-row and 36-cm-row soybean respectively, an average in both years. The highest leaf accumulation area in the upper strata's of the velvetleaf canopies indicates higher efficiency in competition for intercepting the light in comparison with the soybean.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Overall the seedlings that were emerged earlier produced additional biomass. These outcomes were confirmed by the findings of Massinga et al 2001, Puricelli et al 2002and Hock et al, 2005 Leaf areas of velvetleaf plants accumulated in the third and fourth layer 77 % and 71 % for the 50cm-row and 36-cm-row soybean respectively, an average in both years. The highest leaf accumulation area in the upper strata's of the velvetleaf canopies indicates higher efficiency in competition for intercepting the light in comparison with the soybean.…”
Section: Resultssupporting
confidence: 62%
“…Researches have showed that velvetleaf plants which emerged 35 days after soybean planting did not decrease crop yield significantly (Zimdahl, 1988). This indicates the importance of time of velvetleaf seedlings emergence for their survival (Hock et al, 2005), the same was proved also for Digitaria sanguinalis (L.). (Gallart et al, 2010;Oreja and dela Funte.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Practices that improve soyabean competitive ability can be a useful part of an integrated weed management (IWM) programme (Pyon et al. , 1997; Hock et al. , 2005) and a viable option to reduce herbicide applications.…”
Section: Introductionmentioning
confidence: 99%